Image stabilization for in vivo microscopy by high-speed visual feedback control - Lee, Sungon; Nakamura, Yoshihiko; Yamane, Katsu; Toujo, Takeshi; Takahashi, Seiya; Tanikawa, Yoshihisa; Takahashi, Hajime (IEEE-INST ELECTRICAL ELECTRONICS ENGINEERS INC, 2008)
This paper presents image stabilization for microscopy using horizontal visual feedback control of the objective tens through a five-bar linkage and piezoelectric actuators, and its application to in vivo imaging. Even very small in vivo motion due to heartbeat and breathing makes microscopic observation difficult by blurring the microscope image or impossible by sending a region of interest out of view. In order to remove those unwanted effects of the motion, we have introduced motion-canceling robotic technologies into microscopy. Our image stabilization system through motion-canceling provides users with stabilized image sequences with respect to trembling of in vivo subjects. The developed image stabilization system, in term of robotics, corresponds to a visual feedback control system that consists of a robotic mechanism and a high-speed vision. A high-speed camera installed in the microscope detects the motion of the in vivo subject having topically applied fiducials. To virtually cancel this motion, we move the objective lens, synchronizing the motions of the subject and the lens to remove the relative motion between the two. As a result, we observe motion-free images to 10 pm. This technology is one of the very demanding technologies in biological research for in vivo observation with high resolution. In this paper, we verify the effectiveness of the developed system through in vivo experiments.